Strategies to Increase Motoric Ability through Circuit Training Methods in Children with Special Needs: Experimental Study at Sukoharjo State Special School - Jariono, Gatot; Nurhidayat, N; Sudarmanto, Eko; Yunita, Prita; Nugroho, Haris; Maslikah, Uzizatun (Prosiding University Research Colloquium, 2023)
Teaching children with physical, emotional, mental, or social problems who also have special potential intellect and gifts falls under the general heading of special education. Technical education services in the form of special education for children with disabilities or children with very high IQs can be offered at the primary and secondary school levels either inclusively or in the form of special education units. Therefore, there is a need for teachers who have the necessary credentials and are familiar with the traits of kids with learning disabilities, especially kids with special needs. The goal of this project is to apply a circuit-based inclusive education technique to aid the motor skill development of children with exceptional needs. In this examination, a broad research and development strategy was employed. using a quantitative strategy and quasi-experimental techniques. 30 students from Sukoharjo SLB were utilized as research participants, and data was collected through observation, interviews, practical tests, and documentation. Data triangulation techniques were then used for analysis. Data gathering, reduction, and verification, as well as data interpretation. Based on the study's findings, it can be said that circuit training helps children with special needs develop their motor abilities. But more study is required on the topics of adaptive learning, conventional games, social environments, psychological, fine motor abilities, physical fitness, and those connected to inclusive learning in children with special needs.